Translation and Cross-Cultural Adaptation of Expressed Emotion Measure - Tetiana Pastryk; Mykhailo Kots (East European Journal of Psycholinguistics, 2022)
Large gaps of data still exist within the Ukrainian context utilizing Expresses Emotion as a warm, hostile, critical or emotional over-involving behaviour towards individual with a mental or physical condition. The aim of the current article was to suggest translation and cross-cultural adaptation of level of expressed emotion (LEE) as it is perceived by service users.  This study applies the LEE which includes four factors: perceived lack of emotional support (pLES: 19 items), perceived intrusiveness (pIN: seven items), perceived irritation (pIR: seven items), and perceived criticism (pC: five items).  All items are rated according to frequency and intensity on a four-point Likert scale 1 to 4 (1: untrue; 2: somewhat untrue; 3: somewhat true; 4: true). The total score of the 38 items is entitled perceived expressed emotion (pEE). LEE has strong psychometric properties in adolescents and adults.  The translation LEE followed WHO guidelines (2020) and comprises some stages, namely a forward translation from English to Ukrainian, a back translation, expert panel validation, pretesting and cognitive face-to-face interviews with 10 clinical psychologists. The Ukrainian translation version of LEE meets requirements of LEE original version. However, some items were transformed according to semantic, grammatical or stylistic norms of the Ukrainian language. The Ukrainian version of LEE is the first psychometric tool to assess expressed emotion in a Ukrainian healthcare setting.